2020
DOI: 10.3390/su122410484
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance and Comfort Conditions Analysis of a Vernacular Palafitic Timber Building in Portuguese Coastline Context

Abstract: The palafitic timber constructions of the central Portuguese coastline are an example of the adaptation to site-specific conditions (climate and sand landscape morphodynamics) using the available endogenous resources. Thus, in a context of environmental awareness and climate change, it is relevant to understand their features/strategies and how they perform. This work analyses the energy performance and thermal condition evaluation of a vernacular timber building–palheiro–from Praia de Mira, through in situ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…Concerning the indoor temperature, higher mean indoor temperatures were reported in this study than the mean values reported in some of the previous investigations on indoor comfort in buildings built with timber materials [8,11,18,28,42]. However, lower mean temperatures were noted in this study than the average temperatures recorded or predicted in existing research [9,12], especially in some of the buildings in the tropics [43].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Concerning the indoor temperature, higher mean indoor temperatures were reported in this study than the mean values reported in some of the previous investigations on indoor comfort in buildings built with timber materials [8,11,18,28,42]. However, lower mean temperatures were noted in this study than the average temperatures recorded or predicted in existing research [9,12], especially in some of the buildings in the tropics [43].…”
Section: Discussioncontrasting
confidence: 83%
“…However, lower mean temperatures were noted in this study than the average temperatures recorded or predicted in existing research [9,12], especially in some of the buildings in the tropics [43]. The mean RH in the current study is within a similar range to the values obtained from previous investigations [11,28,42]. On the one hand, the neutral temperatures reported in this study are higher than those reported in some studies [11].…”
Section: Discussionsupporting
confidence: 61%
“…Concerning the use of reed as an element for thermal insulation in walls, the walls of palheiros, and the tabique technique are important examples of Portuguese vernacular architecture using reeds. Palheiros are palafitic timber buildings, and although their timber walls usually just have an air cavity, there are records of palheiros in Leirosa (near Figueira da Foz) in which the cavity of the external wall was filled with reeds to improve thermal insulation [8,13] (Figure 2). Reed is also found in earth-filled timber frame walls such as the tabique.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, for example, only the coastal region reaches temperature and humidity conditions similar to those studied. This situation can happen during the summer, for a short time, usually at night (Fernandes et al, 2020). Second, the reed was studied considering the resistance to the mould of the inner face, i.e.…”
Section: Durability Studymentioning
confidence: 99%